Current Use and Future Perspectives of Spatial Audio Technologies in Electronic Travel Aids. (21st March 2018) - Spagnol, Simone; Wersényi, György; Bujacz, Michał; Bălan, Oana; Herrera Martínez, Marcelo; Moldoveanu, Alin; Unnthorsson, Runar
Abstract : Electronic travel aids (ETAs) have been in focus since technology allowed designing relatively small, light, and mobile devices for assisting the visually impaired. Since visually impaired persons rely on spatial audio cues as their primary sense of orientation, providing an accurate virtual auditory representation of the environment is essential. This paper gives an overview of the current state of spatial audio technologies that can be incorporated in ETAs, with a focus on user requirements. Most currently available ETAs either fail to address user requirements or underestimate the potential of spatial sound itself, which may explain, among other reasons, why no single ETA has gained a widespread acceptance in the blind community. We believe there is ample space for applying the technologies presented in this paper, with the aim of progressively bridging the gap between accessibility and accuracy of spatial audio in ETAs.